Ten-year changes in the psychosocial well-being, psychopathology, substance use, suicidality, bullying, and sense of coherence of 18-year-old males: a Finnish population-based time-trend study - Kronström Kim; Multimäki Petteri; Ristkari Terja; Parkkola Kai; Sillanmäki Lauri; Sourander Andre (SPRINGER, 2022)
We studied Finnish 18-year-old males attending obligatory military call-up assessments in 1999 (n = 2340) and 2009 (n = 4309) on time-trend changes in psychosocial well-being, psychopathology, substance use, suicidality, bullying, and sense of coherence. Subjects filled in questionnaires, including the Young Adult Self-Report (YASR) for psychopathology and the Orientation to Life Questionnaire (SOC-13) for sense of coherence. The prevalence of minor mental health problems in the last 6 months decreased from 22.3% in 1999 to 18.6% in 2009 (OR 0.8, 95% CI 0.7-0.9), whereas severe mental health problems remained stable. Suicidal thoughts decreased from 5.7 to 3.7% (OR 0.6, 95% CI 0.5-0.8). The use of illicit drugs decreased from 6.0 to 4.7% (OR 0.8, 95% CI 0.6-0.95), but being drunk at least once a week increased from 10.3 to 13.4% (OR 1.3, 95% CI 1.0-1.5). Attention problems increased in YASR syndrome domains (mean score 2.9 vs 3.2, p < 0.001) and so did somatic complains (mean score 1.7 vs 1.9, p = 0.005). The SOC-13 scores remained stable. The percentage of males who had studied during the past 6 months increased from 91.4 to 93.4% (OR 1.3, 95% CI 1.1-1.6), while being employed decreased from 64.9 to 49.4% (OR 0.5, 95% CI 0.5-0.6). The positive findings included reductions in the prevalence of suicidal thoughts and the use of illicit drugs, but being drunk at least once a week increased. Self-reported somatic problems and attention problems increased. Despite changes in society and family structures, there were only minor overall changes in psychopathology.